Infection with a helminth parasite prevents experimental colitis via a macrophage-mediated mechanism. - FALLON, PADRAIC (The American Association of Immunologists, 2007)
The propensity of a range of parasitic helminths to stimulate a Th2 or regulatory cell-biased response has been proposed to reduce the severity of experimental inflammatory bowel disease. We examined whether infection with Schistosoma mansoni, a trematode parasite, altered the susceptibility of mice to colitis induced by dextran sodium sulfate (DSS). Mice infected with schistosome worms were refractory to DSS-induced colitis. Egg-laying schistosome infections or injection of eggs did not render mice resistant to colitis induced by DSS. Schistosome worm infections prevent colitis by a novel mechanism dependent on macrophages, and not by simple modulation of Th2 responses, or via induction of regulatory CD4+ or CD25+ cells, IL-10, or TGF-. Infected mice had marked infiltration of macrophages (F4/80+CD11b+CD11c?) into the colon lamina propria and protection from DSS-induced colitis was shown to be macrophage dependent. Resistance from colitis was not due to alternatively activated macrophages. Transfer of colon lamina propria F4/80+ macrophages isolated from worm-infected mice induced significant protection from colitis in recipient mice treated with DSS. Therefore, we propose a new mechanism whereby a parasitic worm suppresses DSS-induced colitis via a novel colon-infiltrating macrophage population.
PUBLISHED
Keywords: Clinical Medicine